(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Stratosphericplatforms, geostationary located at altitudes of 17 – 25 km, offer the possibility of becoming a new generation of infrastructural elements for future Earth observation and telecommunication systems. They can act as pseudo- satellites, but with the advantage of being much cheaper and closer to the ground and they can per- form missions that offer greater flexibility. They could be self-launched, easily recovered for maintenance, whenevernecessary, and moved to cover different regions, if desired. They allow a more detailed land vision, due totheir relative closeness to the Earth, at a much lower cost than conventional satellites; furthermore they are geostationary locatedand do not suffer from typical satellite revisiting time limits from 12 h up to 20 days. These platforms could cover a wide range of applications: real-time monitoring of seismic-risks or volcanicareas, early forest fire detection, border securitysurveillance, pipeline, and power-linesurveys; telecommunication servicessuch as cellular-telephone networks,photogram- metry, hydrographicmonitoring system, agriculture monitoring, etc.